Stakeholder perceptions and the influence on sustainability practices in the UK Banking Sector - Ekemezie, Ekene; Echem, Kaodilichukwu Augustine (CV. Kalimasada Group, 2025)
The banking sector in the United Kingdom is at a crossroads, where traditional financial operations are increasingly being scrutinized through the lens of sustainability. This research therefore explored how stakeholders viewed the sustainability efforts of UK banks and whether these perceptions significantly influenced actual practices. A sample of 191 respondents was randomly selected from a population of 2.5 million. Data were gathered using a structured questionnaire and analyzed with mean scores, standard deviations, and T-tests. The instrument showed strong reliability. Ethical guidelines were strictly followed, ensuring informed consent and confidentiality. The study revealed that most stakeholders agreed UK banks are transparent, involve stakeholders in sustainability strategies, prioritize sustainable investments, and communicate initiatives clearly. However, they disagreed that banks would sacrifice financial returns for sustainability. These perceptions suggest that while sustainability is acknowledged, profit still dominates decision-making. A t-test analysis showed no significant influence of stakeholder perception on sustainability practices, supporting the null hypothesis. This implies that although stakeholders view sustainability positively, their perceptions do not substantially impact how banks implement these practices. The findings highlight a potential gap between stakeholder expectations and actual sustainability-driven actions in the UK banking sector. The study concluded that although stakeholders held mostly positive views, these perceptions did not significantly drive sustainability actions within the sector.